Social Media Use Reveals Public Perceptions of Prescribed Burning - Ludie A Bond; Lisa K Lundy; Hope M Miller; Chelsey A Crandall; John M. Diaz; Raelene M Crandall (Journal of Applied Communications, 2024)
Public acceptance and support of prescribed burning is critical for its continued use as an essential and effective land management tool in the southeastern U.S. For this practice to continue and expand, land management agencies and private landowners must have public acceptance and support for prescribed fire policy. Without it, they could face increased burn restrictions, as seen in parts of the western U.S., which might lead to decreased acres burned in the Southeast. Most research on public perceptions of prescribed burning has occurred in the West, but that level of research has been lacking in the Southeast. Our research seeks to fill a knowledge gap in a region where prescribed fires are more frequent than wildfires. To determine the current public perceptions of prescribed fire in the Southeast, we examined social media responses following two prescribed burns that resulted in smoke impacts to two major metropolitan areas in Florida. Data were collected and analyzed from social media platforms for the agencies conducting the burns, emergency response and law enforcement agencies, and traditional media. Our research found that Facebook and X (formerly Twitter) were the primary platforms used by the various agencies with Facebook having the higher number of public engagements. This study culminated in recommendations for improving fire science communication to the public to increase acceptance of prescribed fires on public and private lands and improve fire science policy. We recommend further research due to the rapidly changing environment of science communicators’ use of social media to disseminate information.
Keywords: Keywords: communication platforms; public perception; Uses and Gratifications Theory